Pengaruh Tingkat Pendidikan terhadap Tingkat Kesejahteraan Ekonomi Perempuan Usia Produktif di Kota Tangerang - Cindy Olanda Sari; Neneng Widya; Eka Septika; Fitria Fitria; Asfa Fikria (MUKASI: Jurnal Ilmu Komunikasi, 2025)
The low economic well-being of women of productive age is often associated with inadequate levels of education, especially in Tangerang City. This study focuses on the effect of education level on the economic welfare of productive women in Tangerang City. Using gender equality theory, labor market theory, and human development theory, this research focuses on how education can improve individual economic capabilities. The approach is quantitative with primary statistics in the form of questionnaire results given to 400 women of productive age, further to secondary records within the shape of educational and economic statistical reports from relevant government institutions. The research results show that education is a key factor in increasing income and economic access, but the mismatch between the education obtained and labor market needs is an obstacle to optimizing women's welfare. This research emphasizes the importance of increasing access to quality education that is relevant to the needs of the world of work, as well as supporting programs to help women not only meet their daily financial needs, but also build sustainable economic prosperity through long-term asset management.